A Novel Approach to Density Near-Zero Acoustic Metamaterials - Milan Sečujski; Norbert Cselyuszka; Vesna Crnojević-Bengin (Advances in Materials Science and Engineering)
The study demonstrates the possibility of achieving near-zero propagation of sound waves in acoustic metamaterials based on a membrane-based metamaterial unit cell which exhibits effective mass density of Lorentzian type. The unit cell, which represents the acoustic counterpart of the split ring resonator, was previously used as a building block of left-handed metamaterials, as it exhibits negative density at certain frequencies. In this study we show that its application can be extended to achieving propagation of sound waves at a frequency where its effective density equals zero. This effect can be exploited in a range of applications where extremely low phase variation over long physical distances is required, such as energy tunneling or tailoring the acoustic radiation phase pattern in arbitrary ways. After discussing the dependence of the frequency response of the unit cell on the properties of the host, we show that it can be used to design near-zero acoustic filters with low insertion loss and steep roll-off. Finally, we show that it can be used to achieve simultaneous near-zero propagation at multiple, independently chosen frequencies.